Teacher's Role in Developing Communication and Social-Emotional Skills of Children with Autism Spectrum Disorder - Sudarto, Sudiaryati; Rahmawati, Siti; Choiriyah, Choiriyah (GENIUS: Indonesian Journal of Early Childhood Education, 2023)
This study aims to determine the role of teachers in addressing the communication and social skills of children with Autism Spectrum Disorder along with the implementation of Individualized Education Programs (IEP). This type of research in this article uses a literature study with a qualitative approach. Data collection techniques using literature analysis. Source triangulation is done by searching for data from various sources that are still related to one another. The results of the study show that: 1) Children with ASD experience problems in communication and social-emotional aspects, 2) Children with ASD have very varied conditions, so the approach will be different 3) Communication and social-emotional strategies can be adapted to the school environment according to the needs of children with ASD, 4) Regular (inclusive) schools, the role of the teacher is to provide assistance and focused treatment of the individual autistic child, 5) For mild autistic children, he can still interact and communicate with normal children, while for this severe type, he cannot interact socially and communicate even though he is with his friends..., 6) The application of the IEP (Individualized Educational Program) can accommodate individual barriers because it is an individual program based on the special needs of children in learning so that it can optimize children's potential both in the learning process as well as education as a whole, 7) An autistic people tend to be alone and show preoccupation with their world and minimal eye contact so they don't seem to focus on the surrounding social environment.   Abstrak Penelitian ini bertujuan untuk mengetahui peran guru dalam menangani kemampuan komunikasi dan sosial anak dengan Autism Spectrum Disorder dan penerapan IEP (Individualized Education Program). Jenis penelitian dalam artikel ini menggunakan studi literatur dengan pendekatan kualitatif. Teknik pengumpulan data menggunakan studi kepustakaan.  Triangulasi sumber dilakukan dengan cara mencari data dari beragam sumber yang masih berkaitan satu sama lain.  Hasil penelitian menunjukkan bahwa: 1) Anak dengan ASD mengalami gangguan pada aspek komunikasi dan sosial-emosional, 2) Anak dengan ASD memiliki kondisi yang sangat bervariasi, sehingga pendekatannya pun akan berbeda 3) Strategi komunikasi dan sosial-emosional dapat disesuaikan dengan lingkungan sekolah sesuai dengan kebutuhan anak dengan ASD, 4) Pada sekolah reguler (inklusi), peran guru adalah memberikan pendampingan dan penanganan yang berfokus pada individu anak autis, 5) Untuk anak autis tipe ringan, masih dapat berinteraksi dan berkomunikasi dengan anak normal, Sedangkan untuk tipe berat, mereka tidak dapat berinteraksi sosial dan berkomunikasi meskipun dengan teman-temannya, 6) Penerapan IEP (Individualized Educational Program) dapat mengakomodir hambatan individu karena merupakan program individual yang didasarkan pada kebutuhan khusus anak dalam belajar sehingga dapat mengoptimalkan potensi anak baik dalam proses pembelajaran maupun pendidikan secara keseluruhan, 7) Anak autis cenderung menyendiri dan menunjukkan keasyikan pada dunianya serta kontak mata yang minim sehingga terlihat tidak fokus pada lingkungan sosial di sekitarnya.